SEQUENTIAL EXTRACTION UNTUK PENENTUAN BIOAVAILABILITAS LOGAM Co DAN Ni DALAM SEDIMEN DI KAWASAN PERAIRAN PELABUHAN BENOA DENPASAR BALI - Yulius Leo Adeputra; Emmy Sahara; A. A. I. A. M. Laksmiwati (Program Studi Kimia, FMIPA, Universitas Udayana (Program of Study in Chemistry, Faculty of Mathematics and Natural Sciences, Udayana University), Bali, Indonesia, 2015)
This research was aimed to establish the total concentrations of Ni and Co and then to determine the fractions of various species of the two metals in the sediments. The bioavailability of Co and Ni was determined using sequential extraction technique. The total concentrations of Co and Ni obtained in the sediment were 27.2484 mg/Kg and 41.9458 mg/Kg, respectively. The speciation of Co and Ni found the sediment were 29.83% and 55.86 % in the EFLE fraction; 4.04% and 6.40% in the fraction of Fe / Mn oxides; 13.72 % Co and Ni not detectable in the organic-sulfide fractions; 46.15% and 38.14% in the resistant fraction. Therefore the bioavailability of Co and Ni obtained in the Benoa Port sediment were of 12.9653mg/Kg and 23.3565 mg/Kg respectively.